Recent Developments of 18F-FET PET in Neuro-oncology - Muoio, Barbara; Giovanella, Luca; Treglia, Giorgio (Current Medicinal Chemistry, 2018)
Background: From the past decade to date, several studies related to O-(2- [18F]fluoroethyl)-L-tyrosine (18F-FET) positron emission tomography (PET) in brain tumours have been published in the literature. Objective: The aim of this narrative review is to summarize the recent developments and the current role of 18F-FET PET in brain tumours according to recent literature data. Methods: Main findings from selected recently published and relevant articles on the role of 18F-FET PET in neuro-oncology are described. Results: 18F-FET PET may be useful in the differential diagnosis between brain tumours and non-neoplastic lesions and between low-grade and high-grade gliomas. Integration of 18F-FET PET into surgical planning allows better delineation of the extent of resection beyond margins visible with standard MRI. For biopsy planning, 18F-FET PET is particularly useful in identifying malignant foci within non-contrast-enhancing gliomas. 18F-FET PET may improve the radiation therapy planning in patients with gliomas. This metabolic imaging method may be useful to evaluate treatment response in patients with gliomas and it improves the differential diagnosis between brain tumours recurrence and posttreatment changes. 18F-FET PET may provide useful prognostic information in high-grade gliomas. Conclusion: Based on recent literature data 18F-FET PET may provide additional diagnostic information compared to standard MRI in neuro-oncology.
Keywords: neuroimaging